Relatório de estágio curricular no Departamento de Investigação e Acção Penal da comarca de Lisboa Oeste - Anselmo, Vânia Patrícia Ribeiro (2018)
Firstly, this report focuses on the perception of the judicial reality, focusing on the practical teachings learned during the internship. Secondly, the report focuses on the criminality analysis of domestic violence, aiming at understanding all procedural stages, as well as the existence of the right to refuse to testify that can be exercised applied to any procedural stage in which the victim has to provide statements. Faced with this prerogative, has developed the possibility of applying the regime of declarations for future memory to victims of domestic violence from the Law that develops the legal regime applicable to the prevention of domestic violence. In this case, the situa-tion should be taken into account whenever it is covered by the legal regime of declarations for future memory, anticipating the production of evidence that should be valued at a trial hearing.